2011
DOI: 10.1073/pnas.1019196109
|View full text |Cite
|
Sign up to set email alerts
|

Non-coalescence of oppositely charged droplets in pH-sensitive emulsions

Abstract: Like charges stabilize emulsions, whereas opposite charges break emulsions. This is the fundamental principle for many industrial and practical processes. Using micrometer-sized pH-sensitive polymeric hydrogel particles as emulsion stabilizers, we prepare emulsions that consist of oppositely charged droplets, which do not coalesce. We observe noncoalescence of oppositely charged droplets in bulk emulsification as well as in microfluidic devices, where oppositely charged droplets are forced to collide within ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
102
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 55 publications
3
102
1
Order By: Relevance
“…It was even shown that oppositely charged droplets that are covered by microgels do not coalesce when they are mixed. [3] Furthermore, direct electron microscopy of the microgelcovered interface with freeze-fracture shadow-casting (FreSCa) cryogenic scanning electron microscopy (cryo-SEM) [25] revealed the three-dimensional structure of the microgels at the interface. The particles are strongly deformed at the interface and protrude very little into the oil phase.…”
mentioning
confidence: 99%
“…It was even shown that oppositely charged droplets that are covered by microgels do not coalesce when they are mixed. [3] Furthermore, direct electron microscopy of the microgelcovered interface with freeze-fracture shadow-casting (FreSCa) cryogenic scanning electron microscopy (cryo-SEM) [25] revealed the three-dimensional structure of the microgels at the interface. The particles are strongly deformed at the interface and protrude very little into the oil phase.…”
mentioning
confidence: 99%
“…In addition to these applications, they find increasing use as emulsion stabilizers 31 , where the effects of softness and responsiveness combine to impart new functionalities to emulsions, including extreme compliance and stability under flow 32 or triggered rupture and coalescence 33,34 . The use of microgels as emulsion stabilizers is driven by their strong propensity to adsorb spontaneously at oil-water (o/w) interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…This could be attributed to the fact that dry NPs were prone to shrinking and collapsing. 13,51 The in vitro drug release profiles of the PTX-loaded NPs and PTX-loaded NPs@PDA in the first 30 days are shown in Figure 5. As can be seen from Figure 5, similar drug release curves of PTX-loaded NPs and PTX-loaded NPs@PDA were observed at the same time.…”
mentioning
confidence: 99%